Mentoring Role in Enhancing Yemeni Novice Teachers' Professional Development - kassim , Nabil Amin Mohammed Ahmed; Al-Mekhlafi, Amin Abdullah (International Journal of Language and Literary Studies, 2023)
This study aimed at investigating Yemeni novice teachers' perceptions towards the role of mentoring in their professional development. To achieve the objectives of the study and have a deep insight regarding the study investigation, a mixture of quantitative and qualitative research methods was used by means of an observation checklist and a questionnaire consisting 24 items and administered to 10 novice teachers who were mentored at their schools for six months in the academic year 2020. The findings of the study showed the participants had positive perceptions towards the mentoring role. The participants confirmed that the mentoring process was useful in enhancing their teaching knowledge, updating their instructional methods and use of media, providing them with sufficient instructional and administrative skills regarding classrooms and students' management and performance assessments. Some recommendations were made to schools administrators, policy makers and programs designers to pay more attention novice teachers' needs and demands using formal or informal mentoring practices to improve the quality of English language teaching and learning in Yemeni situation.